ENVIRONMENTAL AWARENESS AND EMPLOYEE GREEN BEHAVIOURS: MEDIATION EFFECT ADAPTIVE LEADERSHIP - Pujianto, Wahyu Eko; Purwono, Rudi; Mudzakkir, Mohammad Fakhruddin; Dyatmika, Sutama Wisnu; Paraswati, Ajeng Dyah; Supriyadi, Supriyadi; Tedyono, Rico; Mayangsari, Agni Shanti (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
Organisations face various environmental challenges that ultimately influence their green practices, particularly among employees. The study aims to test and analyse the effect of environmental awareness on green behavior, with adaptive leadership acting as a mediator. The research was conducted in the food industry in East Java, involving 173 respondents, 32 managers, and 141 employees. The sampling technique was non-probability sampling, with purposive sampling used for sample selection. Data analysis was conducted using quantitative methods, specifically SEM-PLS with Mplus 8 software, to test research hypotheses. The results indicate that environmental awareness has a significant positive effect on employee green behaviour and adaptive leadership. Furthermore, adaptive leadership has a significant positive effect on employee green behaviour. This study also finds that environmental awareness variables positively impact green behaviour, mediated by adaptive leadership in food industry companies in East Java. These findings contribute to the food industry by enhancing green practices, promoting environmental sustainability, and meeting consumer expectations for green products.JEL: D23.